2021
DOI: 10.1371/journal.pone.0254246
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and associated risk factors of COVID-19 infection in dialysis patients in Qatar: A nationwide cohort study

Abstract: Context Patients on maintenance dialysis are more susceptible to COVID-19 and its severe form. We studied the mortality and associated risks of COVID-19 infection in dialysis patients in the state of Qatar. Methods This was an observational, analytical, retrospective, nationwide study. We included all adult patients on maintenance dialysis therapy who tested positive for COVID-19 (PCR assay of the nasopharyngeal swab) during the period from February 1, 2020, to July 19, 2020. Our primary outcome was to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 23 publications
3
25
1
Order By: Relevance
“…Out of 1554 maintenance dialysis patients in the West Bank, 548 acquired COVID-19 during the study period, amounting to 35.3% of the total dialysis population. This rate is much higher than other studies; 7.1% in Qatar [ 11 ] and 12.1% in the United States [ 10 ], for example. This discrepancy might be explained by the variation of the periods through which different studies were conducted; five months in the Qatari study, ten months in the American study and 17 months in ours.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Out of 1554 maintenance dialysis patients in the West Bank, 548 acquired COVID-19 during the study period, amounting to 35.3% of the total dialysis population. This rate is much higher than other studies; 7.1% in Qatar [ 11 ] and 12.1% in the United States [ 10 ], for example. This discrepancy might be explained by the variation of the periods through which different studies were conducted; five months in the Qatari study, ten months in the American study and 17 months in ours.…”
Section: Discussioncontrasting
confidence: 55%
“…To the best of our knowledge, our study is the first of its kind coming from a lower-middle-income country. It is also one of the only very few studies done at a national level [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of acute kidney injury (AKI) secondary to COVID-19 is high [ 85 ] and is strongly associated with high mortality among hospitalized COVID-19 [ 86 88 ]. Ghonimi et al [ 89 ] reported a strong association between death related to COVID-19 infection in dialysis patients, which was also observed in the study of Costa et al [ 90 ], showing that COVID-19 patients with AKI who need dialysis had worse outcomes. Lino et al [ 91 ] also showed that a worse prognosis is frequently associated with a more rapid evolution to intensive and respiratory care or even dialysis.…”
Section: Discussionmentioning
confidence: 70%
“…From a large HD network in India ( n = 14 573), out of 8.8% ( n = 1279) who tested positive for COVID, 22.9% ( n = 293) died most of whom were older patients with multiple comorbidities 116 . Also, a nationwide cohort study from Qatar has reported a higher but non‐statistically significant infection rate as well as COVID‐related deaths in HD compared with PD patients 117 . Although available data on COVID outcomes in patients receiving KRT are scarce in LLMICs, the findings from other regions suggest that PD, which requires minimal interpersonal contact and hospital visits, can be a better KRT modality in a pandemic period.…”
Section: Pd In Setting Of Covid‐19 and Future Pandemicsmentioning
confidence: 99%
“…The good and the bad of telemedicine use on PD in LLMICs identification of complications Physical examination not possible Pre-emptive prescription management statistically significant infection rate as well as COVID-related deaths in HD compared with PD patients 117. Although available data on COVID outcomes in patients receiving KRT are scarce in LLMICs, the findings from other regions suggest that PD, which requires minimal interpersonal contact and hospital visits, can be a better KRT modality in a pandemic period.11 | TELEMEDICINE TO PROMOTE PDTelemedicine and remote monitoring approaches offer the opportunity to address several of the health challenges in the use of PD for LLMICs identified above.…”
mentioning
confidence: 99%